Perancangan Velodrome Balap Sepeda Bertaraf International Di Surabaya (Selasar, 2023)
Facilities that support the talents or interests of the community, especially bicycle racing in East Java, are still inadequate. With this facility, it is hoped that it will be able to accommodate sports activities and national and international competitions. Sports facilities are expected to be able to provide achievements in East Java, especially Surabaya, and accommodate talents or interest from people who want to develop and achieve in the field of bicycle racing. The Velodrome itself has a function as an arena for bicycle racing competitions. It is hoped that athletes with international facilities will be able to excel in the championships that are held.